A polyurethane cold patch storage stability evaluation method based on NCO change and intensity correlation

CN120594810BActive Publication Date: 2026-10-30BEIJING GONGLIANJIEDA HIGHWAY YANGHU ENG CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510781869.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-06-12
Publication Date
2026-10-30
Estimated Expiration
2045-06-12

AI Technical Summary

Technical Problem

目前,这些因素对材料性能的具体影响规律尚未完全明确,存储过程中是否会发生提前反应、失效或性能劣化也尚无定论

Benefits of technology

[0053]本发明的有益效果为:通过构建存储前后NCO消耗率(ΔNCO%)与NCO特征红外峰面积变化率(ΔA%)同存储后1小时马歇尔稳定度(M1h)之间的定量数学模型,实现以冷补料早期强度测试结果为依据,预测化学基团衰减程度,并进一步科学评估其存储稳定性;具备以下显著优势:1、高效性:将评价周期从3至6个月大幅缩短至1小时;2、定量化:借助ΔNCO%、ΔA%和M1h三个关键指标建立联系,实现对材料稳定性等级的精确量化;3、预测性:通过存储后1小时强度数据,有效预判施工后早期强度损失的风险;4、普适性:适用于MDI/TDI基及其他各类聚氨酯冷补料体系;本发明不仅为系统分析不同因素对材料存储性能的影响提供了可靠的定量依据,还为优化聚氨酯冷补料的配方设计及存储管理策略提供了科学支持。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120594810B_ABST
    Figure CN120594810B_ABST
Patent Text Reader

Abstract

The application discloses a kind of based on NCO variation and intensity correlation's polyurethane cold patch material storage stability evaluation method, it is related to road engineering material technical field, the method includes: polyurethane cold patch material finished product is sealed storage and pretreatment at different times, and the sample to be measured participating in different determination test is prepared;The NCO consumption rate of the sample to be measured before and after storage is determined using chemical titration method;The NCO characteristic infrared peak area change rate of the sample to be measured before and after storage is determined using infrared spectroscopy method;The Marshall stability of the sample to be measured before and after storage is tested;The correlation model of NCO consumption rate, NCO characteristic infrared peak area change rate and Marshall stability is established;Based on the Marshall stability of polyurethane cold patch material after storage, storage stability classification standard is formulated.The application realizes early strength test result as basis for cold patch material, predicts chemical group attenuation degree, further scientifically evaluates its storage stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of road engineering materials technology, and in particular to a method for evaluating the storage stability of polyurethane cold patching material based on the correlation between NCO change and strength. Background Technology

[0002] Polyurethane cold patch is a novel road repair material that has seen significant progress in research and application in recent years. Due to its excellent adhesion, elasticity, abrasion resistance, and outstanding weather resistance, it is widely used in road pothole repair projects, especially suitable for repair work in high-standard and harsh environments. A key advantage of this material is its effective application and rapid curing even at low temperatures. Compared to traditional asphalt cold patch, polyurethane cold patch not only maintains good workability at low temperatures but also has a shorter curing time and significantly longer durability, thus its application in the road repair field is becoming increasingly widespread.

[0003] Polyurethane cold patching material is mainly composed of a binder consisting of polyurethane (isocyanate and polyol), diluent, catalyst, plasticizer, etc., as well as aggregates and mineral powder of appropriate gradation. This material has excellent workability, early strength, and durability, and is widely used for the rapid repair of road potholes.

[0004] However, polyurethane cold patching compound is extremely sensitive to moisture, which can react with the isocyanate (NCO) groups in polyurethane. During storage, if the ambient humidity is high, the NCO groups will react with moisture, leading to increased NCO group consumption and thus affecting the application performance of the polyurethane cold patching compound. Furthermore, the performance of polyurethane cold patching compound is significantly affected by various factors such as temperature, humidity, storage time, and packaging conditions. Currently, the specific effects of these factors on material performance are not fully understood, and whether premature reaction, failure, or performance degradation will occur during storage remains inconclusive. Existing evaluation methods mostly rely on observing the degree of clumping after long-term field storage or evaluating the effect after on-site pothole repair, which is time-consuming (usually no less than 3 months) and the results are greatly affected by subjective factors.

[0005] Therefore, there is an urgent need to construct a rapid evaluation system that can quantitatively characterize the correlation between changes in chemical groups and key performance (such as early strength) during storage. Summary of the Invention

[0006] Therefore, it is necessary to provide a method for assessing the storage stability of polyurethane cold-mixed materials based on the correlation between NCO change and strength, in order to address the above-mentioned technical problems.

[0007] This invention provides a method for assessing the storage stability of polyurethane cold-applied fillers based on the correlation between NCO change and strength, comprising:

[0008] S1. The polyurethane cold patch material was sealed and stored for different periods of time and pretreated to prepare test samples for different determination tests.

[0009] S2. The NCO consumption rate of the sample before and after storage was determined by chemical titration.

[0010] S3. Use infrared spectroscopy to determine the rate of change of the area of ​​the characteristic infrared peak of NCO before and after storage of the sample.

[0011] S4. Test the Marshall stability of the sample before and after storage.

[0012] S5. Based on the measurement results of various experiments, establish a correlation model between NCO consumption rate, NCO characteristic infrared peak area change rate and Marshall stability.

[0013] S6. Based on the Marshall stability of polyurethane cold-mixed materials after storage, formulate a standard for classifying storage stability.

[0014] Furthermore, the finished polyurethane cold patch material was sealed and stored for different periods and pretreated to prepare test samples for different determination tests, including:

[0015] S11. Store the finished polyurethane cold patch material in a sealed environment that accelerates aging.

[0016] S12. Set the storage time for sealing different batches of finished cold patch materials, and collect cold patch material samples before sealing and after sealing in batches.

[0017] S13. Using tweezers, scrape three portions of cementing powder of a preset mass from the surface of the cold-filled material sample before and after storage, as the consumption test sample.

[0018] S14. Using tweezers, scrape three portions of cementing powder of a preset mass from the surface of the cold-filled material sample before and after storage, and use them as samples to be tested for characteristic peaks.

[0019] S15. Take three portions of cold patch material of a preset mass from the cold patch material samples before and after storage, and use them as samples to be tested for strength.

[0020] Furthermore, the accelerated aging environment is a sealed environment with an ambient temperature of 40±2℃ and a relative humidity of ≥80%.

[0021] Furthermore, the NCO consumption rate of the test sample before and after storage was determined by chemical titration, including:

[0022] S21. Place the stored consumption sample into a mixed solution of anhydrous toluene and di-n-butylamine-toluene, shake thoroughly until uniformly mixed, and obtain a mixed solution.

[0023] S22. Let the mixed solution stand at room temperature until the consumed amount of the test sample is completely dissolved;

[0024] S23. Add isopropanol to the mixed solution and add bromocresol green indicator dropwise until the mixed solution turns blue. Stop adding the indicator to obtain a blue solution.

[0025] S24. When performing a titration test using a standard hydrochloric acid solution, stop the titration when the color of the blue solution just changes from blue to yellow, and record the volume of standard hydrochloric acid solution consumed.

[0026] S25. Using the amount of the sample to be tested before storage, perform S21-S24 to conduct a blank test;

[0027] S26. Based on the volume of hydrochloric acid standard solution consumed, calculate the NCO consumption of the sample before and after storage using the cold replenishment NCO content formula.

[0028] S27. Based on the NCO consumption of the sample before and after storage, calculate the NCO consumption rate of the cold-filled material after storage.

[0029] Furthermore, the formula for the NCO content of cold-mixed materials is:

[0030]

[0031] In the formula, W is the NCO content; V0 is the volume of hydrochloric acid standard titration solution consumed in the blank test; V s The volume of hydrochloric acid standard titration solution consumed during the sample test is denoted as C; the concentration of the hydrochloric acid standard titration solution is denoted as C; and the mass of the sample to be tested is denoted as m.

[0032] The formula for calculating the NCO consumption rate is:

[0033]

[0034] In the formula, Δ NCO% NCO consumption rate; W 存储前 The amount of NCO in the sample to be tested before storage is the amount consumed; W 存储后 The NCO content in the sample is the amount consumed after storage under different conditions.

[0035] Furthermore, the change rate of the characteristic infrared peak area of ​​NCO before and after storage of the sample was determined using infrared spectroscopy, including:

[0036] S31. Place the sample with characteristic peaks onto the Fourier transform infrared spectrometer for online detection, and set the instrument parameters, including spectral resolution, number of scans, and scanning range.

[0037] S32. Collect the infrared spectrum after online detection, and monitor it at 2252 cm⁻¹. -1 isocyanate groups at the location and 2970cm -1 Quantitative analysis was performed on the changes in the methylene characteristic peak at the location to track the rate of change in the area of ​​the NCO characteristic infrared peak of the sample during storage.

[0038] Furthermore, the formula for calculating the rate of change of the characteristic infrared peak area of ​​NCO is as follows:

[0039]

[0040] In the formula, I1 is 2252cm -1 Characteristic peaks of the -NCO group, from 2100-2400 cm⁻¹ -1 The peak area calculated at the end of storage, with I as the base; 10 2252cm -1 Characteristic peaks of the -NCO group, from 2100-2400 cm⁻¹ -1 The peak area is calculated at the start of storage, with I2 being 2970 cm⁻¹. -1 The characteristic peak of the -CH2 group is located at 2900-3000 cm⁻¹. -1 The peak area calculated at the end of storage, with I as the base; 20 2970cm -1 The characteristic peak of the -CH2 group is located at 2900-3000 cm⁻¹. -1 The peak area is calculated at the start of storage, with as the base.

[0041] Furthermore, the Marshall stability of the test samples before and after storage was tested, including:

[0042] S41. Weigh a predetermined mass of the strength test sample and place it in a container. Spray a predetermined mass of water evenly to ensure that the strength test sample and water are fully mixed to obtain a mixture.

[0043] S42. Transfer the mixture to a Marshall mold and use a tamper to tamp along the perimeter and center of the mold. After tamping, smooth the surface of the sample to be tested.

[0044] S43. Use a Marshall electric compactor to compact the flattened sample to be tested, and then cure the compacted sample at a preset temperature.

[0045] S44. Use a Marshall stabilizer to determine the Marshall stability of the sample to be tested after curing.

[0046] Furthermore, based on the measurement results of various experiments, a correlation model was established between NCO consumption rate, NCO characteristic infrared peak area change rate, and Marshall stability, including:

[0047] S51. Plot the curve showing the relationship between NCO consumption rate and Marshall stability;

[0048] S52. Plot the curve relating the rate of change of the characteristic infrared peak area of ​​NCO to Marshall stability.

[0049] S53. Based on the two plotted relationship curves, establish a correlation model between NCO consumption rate, NCO characteristic infrared peak area change rate, and Marshall stability.

[0050] Furthermore, based on the Marshall stability of polyurethane cold-applied filler after storage, the following storage stability classification criteria were established:

[0051] S61. Test the Marshall stability of the cold-filled material sample and classify the storage stability level according to the intensity test value of the Marshall stability.

[0052] S62. Using the Marshall stability of cold patch material after storage as an evaluation index, assess the storage stability of polyurethane cold patch material.

[0053] The beneficial effects of this invention are: by constructing the NCO consumption rate (Δ) before and after storage NCO% ) and the rate of change of characteristic infrared peak area of ​​NCO (Δ A% Marshall stability (M) after 1 hour of storage 1h A quantitative mathematical model between Δ and Δ allows for the prediction of the degree of chemical group decay based on early strength test results of cold-mixed materials, and further scientific evaluation of their storage stability; it has the following significant advantages: 1. High efficiency: significantly shortens the evaluation cycle from 3 to 6 months to 1 hour; 2. Quantification: using Δ NCO% Δ A% and M 1h Three key indicators are linked to achieve precise quantification of material stability level; 3. Predictive: By storing strength data 1 hour after construction, the risk of early strength loss after construction can be effectively predicted; 4. Universality: Applicable to MDI / TDI based and other types of polyurethane cold patching systems; This invention not only provides a reliable quantitative basis for systematically analyzing the influence of different factors on material storage performance, but also provides scientific support for optimizing the formulation design and storage management strategy of polyurethane cold patching. Attached Figure Description

[0054] The accompanying drawings, which are included to provide a further understanding of the invention and form part of this invention, illustrate exemplary embodiments of the invention and are used to explain the invention, but do not constitute an undue limitation of the invention. In the drawings:

[0055] Figure 1 This is a flowchart of a method for assessing the storage stability of polyurethane cold patching material based on the correlation between NCO change and intensity, according to an embodiment of the present invention.

[0056] Figure 2 This is a schematic diagram of the NCO infrared characteristic peak area variation according to an embodiment of the present invention;

[0057] Figure 3 Δ is according to an embodiment of the present invention NCO% Δ A% With M 1h The correlation model. Detailed Implementation

[0058] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.

[0059] Please see Figure 1 This paper provides a method for assessing the storage stability of polyurethane cold-mixed materials based on the correlation between NCO change and intensity, including:

[0060] S1. The polyurethane cold patch material is sealed and stored for different periods of time and pretreated to prepare test samples for different determination tests.

[0061] In the description of this invention, polyurethane cold patching material is sealed and stored for different periods and pretreated to prepare test samples for different measurement experiments, including:

[0062] S11. Store the finished polyurethane cold patch material in a sealed environment that accelerates aging.

[0063] The accelerated aging environment is a sealed environment with an ambient temperature of 40±2℃ and a relative humidity of ≥80%.

[0064] S12. Set the storage time for sealing different batches of finished cold patch materials, and collect cold patch material samples before sealing and after sealing in different batches.

[0065] Specifically, it is necessary to collect cold patch material samples before storage and cold patch material samples after storage for a period of time (testing cold patch material samples after storage for 1d, 3d, 7d, 30d, 60d, 90d, 180d, and 360d).

[0066] S13. Using tweezers, scrape three portions of cementing powder (approximately 3-5g each) from the surface of the cold-filled material samples before and after storage, as the consumption test samples.

[0067] S14. Using tweezers, scrape three portions of cementing powder (approximately 5-20 mg each) from the surface of the cold-filled sample before and after storage, as samples to be tested for characteristic peaks.

[0068] S15. Take three portions of cold patch material with a preset mass (1220g each) from the cold patch material samples before and after storage, and use them as samples to be tested for strength.

[0069] S2. The NCO consumption rate of the sample before and after storage was determined by chemical titration.

[0070] In the description of this invention, the determination of the NCO consumption rate of the sample before and after storage using chemical titration includes:

[0071] S21. Place the stored amount of the sample to be tested (3-5g) into a 20ml mixture of anhydrous toluene and 10ml of di-n-butylamine-toluene, shake thoroughly until uniformly mixed, and obtain a mixed solution.

[0072] S22. Let the mixed solution stand at room temperature for 30 to 60 minutes until the consumed amount of the test sample is completely dissolved.

[0073] S23. Add 50 ml of isopropanol to the mixed solution, and add bromocresol green indicator dropwise (5-10 drops) until the mixed solution turns blue. Stop adding the indicator to obtain a blue solution.

[0074] S24. Use a 0.5 mol / L hydrochloric acid standard solution to perform a titration test. When the color of the blue solution just changes from blue to yellow, stop the titration and record the volume of hydrochloric acid standard solution consumed.

[0075] S25. Using the amount of the sample to be tested before storage, perform S21-S24 to conduct a blank test.

[0076] S26. Based on the volume of hydrochloric acid standard solution consumed, calculate the NCO consumption of the sample before and after storage using the cold replenishment NCO content formula.

[0077] In the description of this invention, the formula for the NCO content of cold-mixed materials is:

[0078]

[0079] In the formula, W represents the NCO content, in %; V0 represents the volume of hydrochloric acid standard titration solution consumed in the blank test, in ml; V s The volume of standard hydrochloric acid solution consumed during the test is in ml; C is the concentration of the standard hydrochloric acid solution in mol / L; and m is the mass of the sample consumed in g.

[0080] S27. Based on the NCO consumption of the sample before and after storage, calculate the NCO consumption rate of the cold-filled material after storage.

[0081] The formula for calculating the NCO consumption rate is as follows:

[0082]

[0083] In the formula, Δ NCO% NCO consumption rate; W 存储前 The NCO content in the sample before storage is expressed as a percentage (%). 存储后 The NCO content in the sample after storage under different conditions is expressed as a percentage (%).

[0084] S3. Use infrared spectroscopy to determine the rate of change of the area of ​​the characteristic infrared peak of NCO before and after storage of the sample.

[0085] In the description of this invention, the determination of the change rate of the characteristic infrared peak area of ​​NCO before and after storage of the sample using infrared spectroscopy includes:

[0086] S31. Place 5–20 mg of the sample with characteristic peaks sequentially onto the Fourier transform infrared spectrometer for online detection. Set the instrument parameters, including spectral resolution, number of scans, and scan range. For example, set the spectral resolution to 4 cm⁻¹. -1 64 scans, 4000cm scan area -1 ~400cm -1 .

[0087] S32. Collect the infrared spectrum after online detection, and monitor it at 2252 cm⁻¹. -1 The isocyanate group (-NCO) at the position and 2970cm -1 Quantitative analysis was performed by analyzing the changes in the characteristic peak of the methylene (-CH2) group at the NCO region to track the rate of change in the area of ​​the NCO characteristic infrared peak during storage. The changes in the NCO infrared characteristic peak area are shown in the figure below. Figure 2 As shown.

[0088] In the description of this invention, the formula for calculating the rate of change of the area of ​​the characteristic infrared peak of NCO is as follows:

[0089]

[0090] In the formula, I1 is 2252cm -1 Characteristic peaks of the -NCO group, from 2100-2400 cm⁻¹ -1 The peak area calculated at the end of storage, with I as the base; 10 2252cm -1Characteristic peaks of the -NCO group, from 2100-2400 cm⁻¹ -1 The peak area is calculated at the start of storage, with I2 being 2970 cm⁻¹. -1 The characteristic peak of the -CH2 group is located at 2900-3000 cm⁻¹. -1 The peak area calculated at the end of storage, with I as the base; 20 2970cm -1 The characteristic peak of the -CH2 group is located at 2900-3000 cm⁻¹. -1 The peak area is calculated at the start of storage, with as the base.

[0091] S4. Test the Marshall stability of the sample before and after storage.

[0092] In the description of this invention, the Marshall stability of the sample under test before and after storage includes:

[0093] S41. Weigh a predetermined mass of the strength test sample (1220g) and place it in a container. Spray a predetermined mass of water (25g) evenly to ensure that the strength test sample and water are fully mixed to obtain a mixture.

[0094] S42. Transfer the mixture to a Marshall mold and tamp it along the perimeter and center of the mold using a tamper (for example, tamp it 15 times along the perimeter and 10 times in the center to enhance the compactness of the mixture). After tamping, smooth the surface of the sample to be tested.

[0095] S43. Use a Marshall electric compactor to compact the flattened sample to be tested, and then cure the compacted sample at a preset temperature (for example, compact the prepared specimen 75 times on each side, and then cure the compacted cold-filled specimen at 25°C for 1 hour).

[0096] S44. Use a Marshall stabilizer to determine the Marshall stability of the sample to be tested after curing.

[0097] S5. Based on the measurement results of various experiments, establish a correlation model between NCO consumption rate, NCO characteristic infrared peak area change rate and Marshall stability.

[0098] In the description of this invention, based on the measurement results of various experiments, a correlation model is established between NCO consumption rate, NCO characteristic infrared peak area change rate, and Marshall stability, including:

[0099] S51. Plot the curve showing the relationship between NCO consumption rate and Marshall stability.

[0100] S52. Plot the curve relating the rate of change of the characteristic infrared peak area of ​​NCO to Marshall stability.

[0101] S53. Based on the two plotted relationship curves, establish a correlation model between NCO consumption rate, NCO characteristic infrared peak area change rate, and Marshall stability.

[0102] Among them, such as Figure 3 As shown, the mathematical expression for the correlation model is y = 28.62x 0.48 The model's goodness of fit was 90.37%. The correlation model does not consider the effects of storage time, formulation composition, packaging method, etc., and only establishes the relationship between NCO consumption and intensity changes before and after storage, thus using 1-hour intensity to predict storage effect.

[0103] S6. Based on the Marshall stability of polyurethane cold-mixed materials after storage, formulate a standard for classifying storage stability.

[0104] In the description of this invention, the storage stability classification criteria based on the Marshall stability of polyurethane cold-mixed materials after storage include:

[0105] S61. Test the Marshall stability of the cold-filled sample and classify the storage stability level according to the strength test value of the Marshall stability.

[0106] S62. Using the Marshall stability of cold patch material after storage as an evaluation index, assess the storage stability of polyurethane cold patch material.

[0107] Specifically, the storage stability of cold patching materials depends on M 1h The intensity values ​​are divided into the following four levels according to different ranges: when M 1h When the cold-applied material is ≥5kN, there is basically no change, and the storage stability is excellent; when 3kN < M 1h At ≤5kN, the cold-repair material exhibits slight failure, but its storage stability is good; when 0.6kN < M 1h When the load is ≤3kN, the cold-filled material partially fails (approximately 40%), and its storage stability is average; when M 1h When the load is ≤0.6kN, the cold-filled material is basically ineffective and has poor storage stability.

[0108] The present invention will be further described below with reference to specific embodiments.

[0109] In practical applications, polyurethane cold patching materials are widely used in road pothole repair. However, the influence of factors such as temperature, humidity, and storage conditions on its storage stability is not yet clear, and there is a lack of effective quantitative evaluation methods. This application proposes a method for evaluating the storage stability of polyurethane cold patching materials based on the correlation between NCO change and strength.

[0110] The specific implementation method includes the following steps:

[0111] (1) Preparation process of finished polyurethane cold patch material: By precisely controlling the ratio of isocyanate (such as MDI, TDI) to polyol in the formula, a polyurethane prepolymer with an NCO content of 12.5% ​​is prepared. The polyurethane prepolymer, xylene solvent, quartz sand and silane coupling agent are thoroughly stirred at room temperature in the required proportion to prepare a mother liquor. According to the AC-10C gradation requirements, limestone with a particle size of 0-3mm and granite with a particle size of 3-5mm and 5-10mm are prepared. Under room temperature conditions, 6% of the mother liquor is used to thoroughly mix the above aggregates to obtain the finished polyurethane cold patch material.

[0112] (2) Testing Procedure for Finished Polyurethane Cold Patching Material: Use tweezers to evenly scrape 3-5g of binder from the surface of the finished polyurethane cold patching material as a sample; place the sample in a container containing 20ml of anhydrous toluene and 10ml of di-n-butylamine-toluene mixed solution, and shake thoroughly to ensure uniform mixing. Then, let it stand at room temperature for 30-60 minutes until the sample is completely dissolved. Add 50ml of isopropanol to the above solution and add 5-10 drops of bromocresol green indicator until the solution turns blue. Then, titrate with 0.5mol / L hydrochloric acid standard solution. When the solution color just changes from blue to yellow, record the volume of hydrochloric acid standard solution consumed. At the same time, perform a blank test. Based on the volume of hydrochloric acid standard titration solution consumed in the above test, determine the specific NCO content of the finished polyurethane cold patching material according to the NCO content calculation formula. At the same time, use a Fourier transform infrared spectrometer to measure the infrared absorption peak of the sample.

[0113] After the finished polyurethane cold patching material is prepared, it is stored in different packaging methods and under different storage conditions. For details on the specific packaging and storage methods, please refer to the Examples section.

[0114] Example 1

[0115] The finished polyurethane cold patch material was packaged in plastic bags and sealed only with heat-sealed bags, then stored at 25°C for 3 days. After the cold patch material was removed, the NCO content of the stored polyurethane cold patch material was determined according to step (2) in the specific implementation method. Subsequently, the change in NCO consumption of the water-curing cold patch material before and after storage was calculated according to the NCO consumption rate formula. At the same time, infrared spectroscopy was performed on the stored sample, and the consumption of NCO groups was verified by calculation according to the formula. The storage stability of the material was quantitatively evaluated according to the storage stability grading standard of finished polyurethane cold patch material. The specific test results are shown in Table 1.

[0116] Example 2

[0117] The finished polyurethane cold patch material was packaged in plastic bags and sealed only with heat-sealed bags, then stored at 60°C for 3 days. After the cold patch material was removed, the NCO content of the stored polyurethane cold patch material was determined according to step (2) of the specific implementation method. Subsequently, the change in NCO consumption of the water-curing cold patch material before and after storage was calculated according to the NCO consumption rate formula. At the same time, infrared spectroscopy was performed on the stored sample, and the consumption of NCO groups was verified by calculation according to the formula. The storage stability of the material was quantitatively evaluated according to the storage stability grading standard of finished polyurethane cold patch material. The specific test results are shown in Table 1.

[0118] Example 3

[0119] The finished polyurethane cold patch material was packaged in plastic bags, sealed by hot rolling, and then placed in a sealed container. The sealed container was then stored at 25°C for 3 days. After removing the cold patch material, the NCO content of the stored polyurethane cold patch material was determined according to step (2) of the specific implementation method. Subsequently, the change in NCO consumption of the water-curing cold patch material before and after storage was calculated according to the NCO consumption rate formula. Simultaneously, infrared spectroscopy was performed on the stored sample, and the consumption of NCO groups was verified by calculation according to the formula. The storage stability of the material was quantitatively evaluated according to the storage stability grading standard for finished polyurethane cold patch materials. Specific test results are shown in Table 1.

[0120] Example 4

[0121] The finished polyurethane cold patch material was packaged in plastic bags, sealed by hot rolling, and then placed in a sealed container. The sealed container was then stored at 60°C for 3 days. After removing the cold patch material, the NCO content of the stored polyurethane cold patch material was determined according to step (2) of the specific implementation method. Subsequently, the change in NCO consumption of the water-curing cold patch material before and after storage was calculated according to the NCO consumption rate formula. Simultaneously, infrared spectroscopy was performed on the stored sample, and the consumption of NCO groups was verified by calculation according to the formula. The storage stability of the material was quantitatively evaluated according to the storage stability grading standard for finished polyurethane cold patch materials. Specific test results are shown in Table 1.

[0122] Example 5

[0123] The finished polyurethane cold patch material was packaged in aluminum foil bags and sealed using heat-sealing technology, then stored at 25°C for 3 days. After removing the cold patch material, the NCO content of the stored polyurethane cold patch material was determined according to step (2) in the specific implementation method. Subsequently, the change in NCO consumption of the water-curing cold patch material before and after storage was calculated according to the NCO consumption rate formula. At the same time, infrared spectroscopy was performed on the stored sample, and the consumption of NCO groups was verified by calculating according to the formula. The storage stability of the material was quantitatively evaluated according to the storage stability grading standard of finished polyurethane cold patch material. The specific test results are shown in Table 1.

[0124] Example 6

[0125] The finished polyurethane cold patch material was packaged in aluminum foil bags and sealed using heat-sealing technology, then stored at 60°C for 3 days. After removing the cold patch material, the NCO content of the stored polyurethane cold patch material was determined according to step (2) in the specific implementation method. Subsequently, the change in NCO consumption of the water-curing cold patch material before and after storage was calculated according to the NCO consumption rate formula. At the same time, infrared spectroscopy was performed on the stored sample, and the consumption of NCO groups was verified by calculating according to the formula. The storage stability of the material was quantitatively evaluated according to the storage stability grading standard of finished polyurethane cold patch material. The specific test results are shown in Table 1.

[0126] Example 7

[0127] The finished polyurethane cold patch material was packaged in aluminum foil bags and sealed using heat-sealing technology, then stored at 60°C for 30 days. After removing the cold patch material, the NCO content of the stored polyurethane cold patch material was determined according to step (2) in the specific implementation method. Subsequently, the change in NCO consumption of the water-curing cold patch material before and after storage was calculated according to the NCO consumption rate formula. At the same time, infrared spectroscopy was performed on the stored sample, and the consumption of NCO groups was verified by calculating according to the formula. The storage stability of the material was quantitatively evaluated according to the storage stability grading standard of finished polyurethane cold patch material. The specific test results are shown in Table 1.

[0128] The storage performance test results of the water-curing cold patch material in the above embodiments are shown in Table 1:

[0129] Table 1: Test Results of Storage Performance of Finished Polyurethane Cold Repair Material

[0130] Example 1 29.81 30.14 0.73 generally Example 2 42.12 40.56 0.52 Poor Example 3 10.88 11.3 5.61 excellent Example 4 15.37 15.65 4.62 good Example 5 11.70 11.5 5.40 excellent Example 6 5.34 5.50 7.05 excellent Example 7 1.23 1.38 7.92 excellent

[0131] In summary, by utilizing the above-described technical solution of the present invention, the NCO consumption rate (Δ) before and after storage is constructed. NCO% ) and the rate of change of the characteristic infrared peak area of ​​NCO (Δ A% Marshall stability (M) after 1 hour of storage 1hA quantitative mathematical model between Δ and Δ allows for the prediction of the degree of chemical group decay based on early strength test results of cold-mixed materials, and further scientific evaluation of their storage stability; it has the following significant advantages: 1. High efficiency: significantly shortens the evaluation cycle from 3 to 6 months to 1 hour; 2. Quantification: using Δ NCO% Δ A% and M 1h Three key indicators are linked to achieve precise quantification of material stability level; 3. Predictive: By storing strength data 1 hour after construction, the risk of early strength loss after construction can be effectively predicted; 4. Universality: Applicable to MDI / TDI based and other types of polyurethane cold patching systems; This invention not only provides a reliable quantitative basis for systematically analyzing the influence of different factors on material storage performance, but also provides scientific support for optimizing the formulation design and storage management strategy of polyurethane cold patching.

[0132] It should be understood that although the steps in the flowcharts of the accompanying figures are shown sequentially as indicated by the arrows, these steps are not necessarily executed in the order indicated by the arrows. Unless explicitly stated herein, there is no strict order restriction on the execution of these steps, and they can be executed in other orders. Moreover, at least some steps in the flowcharts of the accompanying figures may include multiple sub-steps or multiple stages. These sub-steps or stages are not necessarily completed at the same time, but can be executed at different times, and their execution order is not necessarily sequential, but can be performed alternately or in turn with other steps or at least some of the sub-steps or stages of other steps.

Claims

1. A method for assessing the storage stability of polyurethane cold-mixing materials based on the correlation between NCO change and strength, characterized in that, include: S1. The polyurethane cold patch material was sealed and stored for different periods of time and pretreated to prepare test samples for different determination tests. S2. The NCO consumption rate of the sample before and after storage was determined by chemical titration. S3. Use infrared spectroscopy to determine the rate of change of the area of ​​the characteristic infrared peak of NCO before and after storage of the sample. S4. Test the Marshall stability of the sample before and after storage. S5. Based on the measurement results of various experiments, establish a correlation model between NCO consumption rate, NCO characteristic infrared peak area change rate and Marshall stability. S6. Based on the Marshall stability of polyurethane cold patch material after storage, formulate a storage stability classification standard; The process of sealing and pretreating the finished polyurethane cold patch material for different periods to prepare test samples for different determination tests includes: S11. Store the finished polyurethane cold patch material in a sealed environment that accelerates aging. S12. Set the storage time for sealing different batches of finished cold patch materials, and collect cold patch material samples before sealing and after sealing in batches. S13. Using tweezers, scrape three portions of cementing powder of a preset mass from the surface of the cold-filled material sample before and after storage, as the consumption test sample. S14. Using tweezers, scrape three portions of cementing powder of a preset mass from the surface of the cold-filled material sample before and after storage, and use them as samples to be tested for characteristic peaks. S15. Take three portions of cold patch material of a preset mass from the cold patch material samples before and after storage, and use them as samples to be tested for strength. The method of determining the change rate of the characteristic infrared peak area of ​​NCO before and after storage using infrared spectroscopy includes: S31. Place the sample with characteristic peaks to be tested sequentially on the Fourier transform infrared spectrometer for online detection, and set the instrument parameters, including spectral resolution, number of scans and scanning range; S32. Collect the infrared spectrum after online detection, and monitor it at 2252 cm⁻¹. -1 isocyanate groups at the location and 2970cm -1 The change in the methylene characteristic peak at the location was used for quantitative analysis to track the rate of change in the area of ​​the NCO characteristic infrared peak of the sample during storage. The formula for calculating the rate of change of the characteristic infrared peak area of ​​NCO is as follows: ; In the formula, I1 is 2252cm -1 Characteristic peaks of the -NCO group, from 2100-2400 cm⁻¹ -1 The peak area calculated at the end of storage, with I as the base; 10 2252cm -1 Characteristic peaks of the -NCO group, from 2100-2400 cm⁻¹ -1 The peak area is calculated at the start of storage, with I2 being 2970 cm⁻¹. -1 The characteristic peak of the -CH2 group is located at 2900-3000 cm⁻¹. -1 The peak area calculated at the end of storage, with I as the base; 20 2970cm -1 The characteristic peak of the -CH2 group is located at 2900-3000 cm⁻¹. -1 The peak area is calculated at the start of storage, with as the base.

2. The method for assessing the storage stability of polyurethane cold-mixing materials based on the correlation between NCO change and strength, as described in claim 1, is characterized in that... The accelerated aging environment is a sealed environment with an ambient temperature of 40±2℃ and a relative humidity of ≥80%.

3. The method for assessing the storage stability of polyurethane cold-mixing materials based on the correlation between NCO change and strength, as described in claim 1, is characterized in that... The NCO consumption rate of the sample before and after storage, determined by chemical titration, includes: S21. Place the stored consumption sample into a mixed solution of anhydrous toluene and di-n-butylamine-toluene, shake thoroughly until uniformly mixed, and obtain a mixed solution. S22. Let the mixed solution stand at room temperature until the consumed amount of the test sample is completely dissolved; S23. Add isopropanol to the mixed solution and add bromocresol green indicator dropwise until the mixed solution turns blue. Stop adding the indicator to obtain a blue solution. S24. When performing a titration test using a standard hydrochloric acid solution, stop the titration when the color of the blue solution just changes from blue to yellow, and record the volume of standard hydrochloric acid solution consumed. S25. Using the amount of the sample to be tested before storage, perform S21-S24 to conduct a blank test; S26. Based on the volume of hydrochloric acid standard solution consumed, calculate the NCO consumption of the sample before and after storage using the cold replenishment NCO content formula. S27. Based on the NCO consumption of the sample before and after storage, calculate the NCO consumption rate of the cold-filled material after storage.

4. The method for evaluating the storage stability of polyurethane cold-mixing materials based on the correlation between NCO change and strength, as described in claim 3, is characterized in that... The formula for the NCO content of the cold-mixed material is: ; In the formula, W is the NCO content; V0 is the volume of hydrochloric acid standard titration solution consumed in the blank test; V s The volume of hydrochloric acid standard titration solution consumed during the sample test is denoted as C; the concentration of the hydrochloric acid standard titration solution is denoted as m; and the mass of the sample to be tested is denoted as m. The formula for calculating the NCO consumption rate is as follows: ; In the formula, Δ NCO% NCO consumption rate; W 存储前 The amount of NCO in the sample to be tested before storage is the amount consumed; W 存储后 The NCO content in the sample is the amount consumed after storage under different conditions.

5. The method for assessing the storage stability of polyurethane cold-mixing materials based on the correlation between NCO change and strength, as described in claim 1, is characterized in that... The Marshall stability of the sample under test before and after storage includes: S41. Weigh a predetermined mass of the strength test sample and place it in a container. Spray a predetermined mass of water evenly to ensure that the strength test sample and water are fully mixed to obtain a mixture. S42. Transfer the mixture to a Marshall mold and use a tamper to tamp along the perimeter and center of the mold. After tamping, smooth the surface of the sample to be tested. S43. Use a Marshall electric compactor to compact the flattened sample to be tested, and then cure the compacted sample at a preset temperature. S44. Use a Marshall stabilizer to determine the Marshall stability of the sample to be tested after curing.

6. The method for assessing the storage stability of polyurethane cold-mixing materials based on the correlation between NCO change and strength, as described in claim 1, is characterized in that... The correlation model established based on the measurement results of various experiments, concerning NCO consumption rate, NCO characteristic infrared peak area change rate, and Marshall stability, includes: S51. Plot the curve showing the relationship between NCO consumption rate and Marshall stability; S52. Plot the curve relating the rate of change of the characteristic infrared peak area of ​​NCO to Marshall stability. S53. Based on the two plotted relationship curves, establish a correlation model between NCO consumption rate, NCO characteristic infrared peak area change rate, and Marshall stability.

7. The method for assessing the storage stability of polyurethane cold-mixing materials based on the correlation between NCO change and strength, as described in claim 1, is characterized in that... The criteria for classifying storage stability based on the Marshall stability of polyurethane cold-applied materials include: S61. Test the Marshall stability of the cold-filled material sample and classify the storage stability level according to the intensity test value of the Marshall stability. S62. Using the Marshall stability of cold patch material after storage as an evaluation index, assess the storage stability of polyurethane cold patch material.

Citation Information

Patent Citations

  • Urethane curable composition

    CN104662058A

  • Normal-temperature reaction type cold patch material as well as preparation method and application thereof

    CN117923833A